Design and Development Job Fair Application at STIKES Dr.Soetomo Hospital Foundation Surabaya - Nugraha, Badai Satria; Nurcahyawati, Vivine; Suhandiah, Sri (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Job fair is central to places job offer. Job fair is important in providing job vacancy for alumnus. But there are the problem in STIKES foundation hospital Dr. Soetomo surabaya, the alumnus cannot know information job opportunities right away and detail, The number of a letter vacancy who come on UKSPBK&A is different than administration general and UKSPBK&A cannot be knowing the number and anyone who applied and received work in every vacancy, and agencies could not know whether a vacancy they send was approved for received or not. To solve that problems, STIKES need made application job fair. Application is capable of accessed by UKSPBK&A, alumnus and agencies through facilities web. So that can reach all users and processing job fair which more easily and fast. Making this applications using methods sdlc waterfall. The results of the tryouts this application is system  can organize job vacancy. Help to provide a realtime vacancy work and providing function applied job vacancy. And can produce report applicants , the reports of alumni who applied and received on each vacancy.